Traditional is Innovative: Redefining the Role of Conventional Building Materials and Construction Methods - Neha Korde; Prachi Patel; Shalini Sheoran (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Conventional building materials and construction methods are losing their significance in vernacular settlements in an attempt to be modern. In urbanisation, smaller settlements are losing their cultural identity and traditional craftsmanship in their building elements while adopting fashionable building materials, negating the regional construction methods, which can be defined as intangible cultural heritage in this project. The paper studies a few architectural practices that have defined their latest ideas and visions based on these conventional building materials and construction methods to revive and retain traditional knowledge through their work.  The documentation exercise in each academic semester becomes the focal point for extracting knowledge and utilising the outcomes to transform and nurture it today. The paper explores the form of these contemporary practices, which follows the “theory - research - hands-on practice” format, and the changing role of the architect as a conscious designer to retain and transfer the cultural heritage to their peers, the community and the next generation for a better future.